Isolated skeletal ossicles of a new brittlestar of the Family Cheiropterasteridae Spencer, 1934 (Echinodermata: Ophiuroidea) in the Lower Devonian of Bohemia (Czech Republic) - Hotchkiss,F.H.C.; Prokop,R.J.; Petr,V. (Journal of the Czech Geological Society, 1999)
Isolated ophiuroid ambulacrals have been discovered in washings from the so-called 'white beds' of Lower Devonian limestones of the Barrandian area. They are unusual because they are sculptured and represent structural analogue of biserially arranged and alternating arm plates of many Devonian crinoids. We interpret these ambulacrals as belonging to a new species of the Family Cheiropterasteridae Spencer, 1934.
Keywords: micropalaeontology; Echinodermata; Ophiuroidea; Cheiropterasteridae; isolated ambulacrals; Lower Devonian; Bohemia